RESPON PERTUMBUHAN DAN HASIL MENTIMUN TERHADAP PEMBERIAN POC LIMBAH CAIR TAHU DAN DOSIS PUPUK PETROGANIK - Marsinah, Marsinah; Abdarah, Abdarah (Fakultas Pertanian, Universitas Janabadra, 2024)
Cucumber (Cucumis sativus L.) is a type of fruit vegetable that has many benefits, so demand for cucumber commodities is very rapid. One way to increase cucumber production is through fertilization. This research aims to determine the effect of giving OLC (Organic Liquid Compost) liquid tofu waste and doses of petroganic fertilizer on the growth and yield of cucumber plants. The experimental design used was a factorial randomized block design (RBD) with two factors. The first factor, namely the dose of petroganic fertilizer, consists of 3 treatment levels, namely: P1: 1 ton/ha (2.5 g/plant); P2: 2 tons/ha (5 g/plant); P3: 3 tonnes/ha (7.5 g/plant). The second factor, namely the interval for administering OLC for tofu liquid waste, consists of 3 levels of treatment, namely: I1: OLC for tofu liquid waste fertilization at intervals of 7 days; I2: POC liquid waste tofu fertilization interval 9 days; I3: POC liquid waste knows to fertilize every 12 days. Observation variables include plant height, plant height growth rate, number of leaves, growth rate of leaf number, number of fruit, fruit weight and fruit length. The results showed that the treatment dose of petroganic fertilizer was not significantly different from all observed variables. Meanwhile, the treatment interval for administering OLC for tofu liquid waste was significantly different for all observation variables. And there was no interaction between the two treatments. Keywords: cucumber, petroganik; tofu liquid waste olc INTISARI Mentimun (Cucumis sativus L.) merupakan jenis sayuran buah yang memiliki banyak manfaat, sehingga permintaan terhadap komoditi mentimun sangat pesat. Salah satu cara untuk meningkatkan produksi mentimun, yaitu melalui pemupukan. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian POC limbah cair tahu dan dosis pupuk petroganik terhadap pertumbuhan dan hasil tanaman mentimun. Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok (RAK) Faktorial dengan dua faktor. Faktor pertama yaitu dosis pupuk petroganik terdiri atas 3 aras perlakuan, yaitu: P1 : 1 ton/ha (2,5 g/pertanaman); P2: 2 ton/ha (5 g/per tanaman); P3: 3 ton/ha (7,5 g/per tanaman). Faktor kedua yaitu interval pemberian POC limbah cair tahu terdiri atas 3 aras perlakuan, yaitu: I1: POC limbah cair tahu pemupukan selang 7 hari; I2: POC limbah cair tahu pemupukan selang 9 hari; I3: POC limbah cair tahu pemupukan selang 12 hari. Variabel pengamatan meliputi tinggi tanaman, laju pertumbuhan tinggi tanaman, jumlah daun, laju pertumbuhan jumlah daun, jumlah buah, bobot buah dan panjang buah. Hasil penelitian menunjukkan bahwa perlakuan dosis pupuk petroganik tidak berbeda nyata terhadap semua variabel pengamatan. Sedangkan perlakuan interval pemberian POC limbah cair tahu berbeda nyata terhadap semua variabel pengamatan. Dan tidak terjadi interaksi diantara kedua perlakuan. Kata kunci: mentimun; petroganik; poc limbah cair tahu